ANALISA CACAT COR PADA PROSES PENGECORAN BURNER KOMPOR - Atmadja, Sugeng Tirta (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2006)
Objective of this research is to analyse casting defect in burner casting process. The research have been conducted in Small Medium Enterprise PT. Suyuti Sido Maju. Casting deffects were observeb by visual inspection. There are some casting deffect such as : cold shut, shearing and void.Composition of casting product, pouring temperature and characterization of sand casting have been done to investigate the casting process that caused casting deffect.